2015
DOI: 10.1134/s1063776115010094
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of the sticking time and sticking probability of Rb atoms on a polydimethylsiloxane coating

Abstract: We present the results of a systematic study of Knudsen's flow of Rb atoms in cylindrical capillary cells coated with a polydimethylsiloxane (PDMS) compound. The purpose of the investigation is to deter mine the characterization of the coating in terms of the sticking probability and sticking time of Rb on the two types of coating of high and medium viscosities. We report the measurement of the sticking probability of a Rb atom to the coating equal to 4.3 × 10 -5 , which corresponds to the number of bounces 2.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…By using the average numbers measured, it is possible to estimate the distance X that polarized Rb atoms need to penetrate inside the tube and to relax completely on the paraffin surface. The distance can be written as [33]:…”
mentioning
confidence: 99%
“…By using the average numbers measured, it is possible to estimate the distance X that polarized Rb atoms need to penetrate inside the tube and to relax completely on the paraffin surface. The distance can be written as [33]:…”
mentioning
confidence: 99%
“…21 Changes to the loading process or the addition of anti-relaxation wall coatings or buffer gases can greatly mitigate the transport problems and increase the overall absorption, 22 but even the coated cells require a "ripening" time before proper operation. 23 Since Rb is taken as an extreme case, such changes may not be necessary in applications monitoring less reactive gases.…”
mentioning
confidence: 99%
“…By analyzing the cell thickness dependence of the motional averaged light shift, they found that 𝜏 w of Rb atoms on octadecyltrichlorosilane (OTS) coated Pyrex surface was about 0.53 µs at a temperature of 103 ∘ C. Due to the fact that their cells contained several torrs of nitrogen as velocity changing buffer gas, it raised the question whether the presence of nitrogen might alter the surface adsorption behavior of Rb atoms. [11] Atutov et al [12] studied the diffusion of Rb vapor through long coated capillary tubes, and found that 𝜏 w of Rb atoms on a polydimethylsiloxane (PDMS) coating was about 20-50 µs depending on the viscosity of the coating material. Freitas et al [13] studied the adsorption and desorption of Cs atoms on a fused-quartz surface using pump-probe evanescent wave spectroscopy.…”
mentioning
confidence: 99%